2015
DOI: 10.1111/jsap.12375
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of intra‐abdominal eumycotic mycetoma caused by Penicillium duponti in a dog

Abstract: A 2-year-old female neutered golden retriever was presented for investigation of an intra-abdominal mass. Computed tomography revealed a mass associated with the caudal pole of the right kidney. Incisional biopsy findings were consistent with eumycotic mycetoma. The mass was subsequently removed in conjunction with right ureteronephrectomy. Two years later, the dog re-presented with a splenic mass and fungal plaques located throughout the peritoneum. Splenectomy was performed and the mass was diagnosed as eumy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Eumycetomas are chronic pyogranulomatous lesions caused by moulds, frequently reported in humans living in tropical and subtropical environments (e.g. Madura Foot) but rarely in dogs [[1], [2], [3], [4], [5], [6]]. Usually restricted to subcutaneous tissues, there have been only two reports of cases involving intra-abdominal lesions in dogs [[4], [5], [6]].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Eumycetomas are chronic pyogranulomatous lesions caused by moulds, frequently reported in humans living in tropical and subtropical environments (e.g. Madura Foot) but rarely in dogs [[1], [2], [3], [4], [5], [6]]. Usually restricted to subcutaneous tissues, there have been only two reports of cases involving intra-abdominal lesions in dogs [[4], [5], [6]].…”
Section: Introductionmentioning
confidence: 99%
“…Madura Foot) but rarely in dogs [[1], [2], [3], [4], [5], [6]]. Usually restricted to subcutaneous tissues, there have been only two reports of cases involving intra-abdominal lesions in dogs [[4], [5], [6]]. These were associated with the uterine stump and the caudal aspect of the right kidney, caused by Madurella mycetomatis and Penicillium duponti respectively [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, susceptibility was tested only for the latter isolate resulting in an inhibition zone of 30 mm, probably indicating that, contrary to the in vivo lack of activity, in vitro the fungus was still susceptible to the drug. More recently, Janovec et al [85] reported the successful treatment with itraconazole of a dog with visceral mycetoma caused by Penicillium duponti.…”
Section: Moldsmentioning
confidence: 99%